Retention, engagement, and binge‐eating outcomes: Evaluating feasibility of the Binge‐Eating Genetics Initiative study. Issue 8 (2nd May 2022) - Flatt, Rachael E.; Thornton, Laura M.; Smith, Tosha; Mitchell, Hannah; Argue, Stuart; Baucom, Brian R. W.; Deboeck, Pascal R.; Adamo, Colin; Kilshaw, Robyn E.; Shi, Qinxin; Tregarthen, Jenna; Butner, Jonathan E.; et al.
Abstract: Objective: Using preliminary data from the Binge‐Eating Genetics Initiative (BEGIN), we evaluated the feasibility of delivering an eating disorder digital app, Recovery Record, through smartphone and wearable technology for individuals with binge‐type eating disorders. Methods: Participants ( n = 170; 96% female) between 18 and 45 years old with lived experience of binge‐eating disorder or bulimia nervosa and current binge‐eating episodes were recruited through the Recovery Record app. They were randomized into a Watch (first‐generation Apple Watch + iPhone) or iPhone group; they engaged with the app over 30 days and completed baseline and endpoint surveys. Retention, engagement, and associations between severity of illness and engagement were evaluated. Results: Significantly more participants in the Watch group completed the study ( p = .045); this group had greater engagement than the iPhone group ( p 's < .05; pseudo‐ R 2 McFadden effect size = .01–.34). Overall, binge‐eating episodes, reported for the previous 28 days, were significantly reduced from baseline (mean = 12.3) to endpoint (mean = 6.4): most participants in the Watch (60%) and iPhone (66%) groups reported reduced binge‐eating episodes from baseline to endpoint. There were no significant group differences across measures of binge eating. In the Watch group, participants with fewer episodes of binge eating at baseline were more engaged ( p 's < .05; pseudo‐ R 2 McFadden = .01–.02). Engagement did not significantly predict binge eating at endpoint nor change in binge‐eating episodes from baseline to endpoint for both the Watch and iPhone groups. Discussion: Using wearable technology alongside iPhones to deliver an eating disorder app may improve study completion and app engagement compared with using iPhones alone.